2012
DOI: 10.1007/s00216-012-5829-6
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Raman biosignatures by ionising radiation and the implications for life detection on Mars

Abstract: Raman spectroscopy has proven to be a very effective approach for the detection of microorganisms colonising hostile environments on Earth. The ExoMars rover, due for launch in 2018, will carry a Raman laser spectrometer to analyse samples of the martian subsurface collected by the probe's 2-m drill in a search for similar biosignatures. The martian surface is unprotected from the flux of cosmic rays, an ionising radiation field that will degrade organic molecules and so diminish and distort the detectable Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 56 publications
2
56
0
Order By: Relevance
“…The peak assignments of the relevant vibrational modes are given in Table 2. As expected, (Vítek et al, 2009a) 1157 (1156) (Dartnell et al, 2012) 1152 (1155) (C-C) str 1003 (1005) (C-CH 3 ) bend Wavenumbers in parentheses refer to this work. sym, symmetric; str, stretch; bend, bending.…”
Section: Analyses and Resultssupporting
confidence: 82%
“…The peak assignments of the relevant vibrational modes are given in Table 2. As expected, (Vítek et al, 2009a) 1157 (1156) (Dartnell et al, 2012) 1152 (1155) (C-C) str 1003 (1005) (C-CH 3 ) bend Wavenumbers in parentheses refer to this work. sym, symmetric; str, stretch; bend, bending.…”
Section: Analyses and Resultssupporting
confidence: 82%
“…Recent studies have indicated that the martian surface radiation environment will likely cause the degradation of carotenoids and similar biomolecules, altering the Raman spectra of any such biosignatures that may be present on Mars (Dartnell et al, 2012). Ancient deposits of reduced carbon, however, are less likely to be affected by solar UV radiation and cosmic rays, providing a potentially more robust marker of habitat and biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids play many vital roles in a large number of prokaryotic and eukaryotic microorganisms: they participate in energy-harvesting complexes, protect cells against damage by short-wavelength visible and UV radiation, and help repair cellular damage (33). They represent a diverse group of chemicals with a conjugated polyene skeletal backbone.…”
Section: Raman Spectrometry Of Microbial Pigments-pure Culture Studiesmentioning
confidence: 99%
“…They represent a diverse group of chemicals with a conjugated polyene skeletal backbone. The presence of this polyene backbone enhances the Raman signals, permitting the detection of extremely small amounts of carotenoids (33,34). The first RRS of carotenoids were reported from 1970 on (23,26).…”
Section: Raman Spectrometry Of Microbial Pigments-pure Culture Studiesmentioning
confidence: 99%